Dylematy moralne polskich aptekarzy - Grychtoł, Anna (Annales. Etyka w Życiu Gospodarczym, 2015)
A comprehensive work that would be focused on the moral dilemmas of the pharmacists has not been published yet. The pharmacist profession is commonly perceived as an occupation associated with such virtues as calmness, precision and accuracy. However, there is a lack of knowledge on the moral dilemmas the pharmacist contends with. One of the reasons lies in the fact that some citizens of our country, especially the younger generation, do not recognise the difference between the profession of pharmacist and the profession of salesperson. On the other hand, as M. Brazier indicates, the majority of scientific works are almost exclusively concentrated on the ethical dilemmas of ‘high drama’ and ‘low incidence’. In that context the work of pharmacist appears to be imbued with the ‘small dramas’ taking place every day. Therefore, it seems to be necessary to point out what duties or conflicts of values the Polish pharmacist faces and to make an attempt to find appropriate ways to solve them.